The Effects of Tai Chi Training in Patients with Heart Failure: A Systematic Review and Meta-Analysis - Ren, Xiaomeng; Li, Yanda; Yang, Xinyu; Li, Jie; Li, Huilong; Yuan, Zhengzhong; Sun, Yikun; Shang, Hongcai; Xing, Yanwei; Gao, Yonghong (Frontiers in Physiology, 2017)
Increasing population have more than one cardiovascular disease, and Heart Failure (HF) is one of the most common and serious diseases. We performed a meta-analysis to determine the effects of TC in patients with HF. Clinical trials that randomized HF patients to Tai Chi (TC) therapy versus conventional care, other trainings were included for analysis. Electronic literature search of PubMed was conducted from their inception until September 17, 2015. In Addition, we performed hands searches of the China national knowledge infrastructure (CNKI), and WanFang Data from their inception until August 28, 2015. A total of 11 trials with 656 patients were available for analysis. The results suggested that TC was associated with a significantly improved 6-min walk distance (6MWD, weighted mean difference (WMD) 65.29 m; 95%CI 32.55-98.04) and quality of life (Qol, WMD -11.52 points; 95% CI -16.5 to -6.98) and left ventricular ejection fraction (LVEF, WMD 9.94%; 95% CI 6.95 to 12.93). TC was shown to reduce serum B-type natriuretic peptide (BNP, standard mean difference (SMD) -1.08 pg/mL; 95% CI -1.91 to -0.26) and heart rate (HR, WMD -2.52 bpm; 95% CI -3.49 to -1.55). In summary, our meta-analysis demonstrated the clinical evidence about TC for HF is inconclusive. TC may improve 6MWD, Qol, LVEF in patients with HF and could reduce BNP, HR. However, there is currently a lack of evidence to support TC altering other important clinical outcomes. Further larger randomized controlled trials (RCTs) are urgently needed to investigate the effects of TC.